Chiral Lewis Acid-Catalyzed Asymmetric Multicomponent Michael Reaction through [1,2]-Phospha-Brook Rearrangement - Lin, Qianchi; Wang, Siyuan; Weng, Rui; Cao, Weidi; Feng, Xiaoming (Organic letters, 2023)
The multicomponent catalytic asymmetric Pudovik addition/[1,2]-phospha-Brook rearrangement/Michael reaction sequence of isatins, phosphites, and 4-oxobutenoates was realized. A series of oxindole derivatives containing two contiguous stereocenters was obtained in high yields and excellent stereoselectivities (up to >99% yield, >95:5 dr, >99% ee) using a chiral Lewis acid catalyst. A possible catalytic model is presented to illustrate the stereocontrol.